2020
DOI: 10.1155/2020/8732473
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Culturable Aerobic Bacteria in the Midgut of Field-Caught Culex tritaeniorhynchus, Culex gelidus, and Mansonia annulifera Mosquitoes in the Gampaha District of Sri Lanka

Abstract: Background. Larval and adult mosquito stages harbor different extracellular microbes exhibiting various functions in their digestive tract including host-parasite interactions. Midgut symbiotic bacteria can be genetically exploited to express molecules within the vectors, altering vector competency and potential for disease transmission. Therefore, identification of mosquito gut inhabiting microbiota is of ample importance before developing novel vector control strategies that involve modification of vectors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…The predominant microbiome in Cx. tritaeniorhynchus in Sri Lanka comprised Erwiniaceae, Staphylococcaceae, and Bacillaceae [36], which aligns with our current study. However, Bacillaceae was absent in domestic mosquitoes.…”
Section: Discussionsupporting
confidence: 92%
“…The predominant microbiome in Cx. tritaeniorhynchus in Sri Lanka comprised Erwiniaceae, Staphylococcaceae, and Bacillaceae [36], which aligns with our current study. However, Bacillaceae was absent in domestic mosquitoes.…”
Section: Discussionsupporting
confidence: 92%
“…and Ae. aegypti (Pidiyar et al 2004;Apte-Deshpande et al 2012;Gunathilaka et al 2020;Giraud et al 2022); Stenotrophomonas maltophilia and Xenophilius have been observed in An. stephensi and Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Under the paratransgenesis approach, Bacillus megaterium and B. licheniformis have been identified previously as suitable candidates for phlebotomine sand flies [ 60 , 61 ]. In the present study, several Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The gut flora among insects is highly dynamic [ 65 ], which may have influenced the present findings. Only 20% of the bacteria in the gut environment can be grown on culture media according to the literature [ 61 ]. This is a limitation of the culture-dependent analysis, which does not allow an estimation of the whole gut bacterial community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation